A 'particular history' of English language teaching in nineteenth-century Spain: the Board of Commerce School of English in Barcelona (1826–1851). (2nd January 2017) - Lombardero Caparrós, Alberto
Abstract: The present article seeks to fill a gap in the history of English-language teaching in Spain by delving into a key nineteenth-century Catalan institution called the Board of Commerce, forerunner of the current Chamber of Commerce of Barcelona, with specific attention to the origins and early development of the Board of Commerce School of Languages. The microhistory of the School of English (1826–1851) forms the central focus of this study, which constitutes a 'particular' history of language teaching of the sort recommended by Stern (1983: 83). Topics including typology of students and textbooks used in class are considered, as is the methodology followed by the only teacher of English throughout the 25 years of the School's existence, William Casey (1795–1857). To achieve that, all the original documents on the Board of Commerce School of English, held at the Library of Catalonia (Barcelona), were perused bringing to light some key documents such as the School of English monthly reports and Casey's teaching plan. From a relatively 'macro-historical' perspective, Casey's English-teaching methodology is assessed in relation to the ideas of leading European foreign language innovators of the time such as Hamilton, Ahn, and Ollendorff. In that regard, the results show that Casey's methodology bears a resemblance to the ones put forward by those innovators, thus indicating Casey's eclecticism as far as English-language teaching is concerned.